Atlas of liposuction - Aiache, Adrien E.; Shiffman, Melvin A. (New Delhi : Jaypee-Highlights, 2013)
Liposuction is a procedure in cosmetic surgery that breaks up excess body fat, which is then removed through a cannula inserted under the skin. Atlas of Liposuction is a comprehensive guide to the current techniques for liposuction. Beginning with an introduction to the history and set up of the procedure, the following chapters discuss liposuction in different parts of the body and post-operative management. Each procedure is described in a step by step manner, detailing incisions, positions, instruments, anaesthesia, preoperative care and the actual operative technique. Written by highly experienced plastic surgeons from California, this exhaustive atlas features nearly 740 full colour photographs and illustrations showing actual clinical cases. Key
Keywords: LIPOSUCTION -- ATLAS; LIPOSUCCIÓN -- ATLAS